HUBUNGAN STATUS IMUNISASI, STATUS GIZI, DAN PRILAKU MEROKOK DENGAN KEJADIAN ISPA PADA BALITA UMUR 1–3 TAHUN - Jusmiarti, Jusmiarti (Universitas Fort de Kock Bukittinggi, 2023)
ARI is the most common disease suffered by children and all children can experience it. This can be caused the immune system of children is more vulnerable than adults. The number of toddlers at Air Bangis Community Health Center suffering from ARI is 7,226 people in 2021. The purpose of the study was to determine the correlation between Immunization Status, Nutritional Status and Smoking Behavior with the incidence of ARI in Toddlers Age 1 – 3 Years in the Working Area of Air Bangis Community Health Center, Pasaman Barat Regency in 2022. This study was Analytical Descriptive with Cross Sectional design. In this study, the sample was taken using the Stratified Random Sampling method with a total sample of 66 people. This research was conducted in August 2022 in the Working Area of Air Bangis Community Health Center, Pasaman Barat Regency. Data processing was done by using a computer to determine the correlation among variables. From the results of the study, it was found that respondents had incomplete immunizations (53.0%), immunization status with normal weight (69.0%), smoking behavior did not pay attention to surroundings (62.1%), ARI incidence (63.6%). The results of the bivariate analysis showed that the immunization status p-value = 0.030, OR = 3.600, Nutritional Status p-value = 0.036, OR = 4.760, smoking behavior p-value = 0.000, OR = 10.321 on the incidence of ARI in children under five. From the results of the study, it can be concluded that there is a significant correlation between immunization status, nutritional status, and smoking behavior on the incidence of ARI in children under five. It is recommended that parents can provide complete immunizations, provide healthy and nutritious food, and not smoke in the house.Keywords: ARI, Immunization, Nutritional Status, Smoking